Semi-fragile watermarking for automatic detection of engineering drawing modifications in collaborative design. Issue 5 (2nd September 2016) - Chen, Yong-Fu; Sun, Cheng; Shen, Jia-Qi; Huang, Zheng-Dong; Chen, Li-Ping
ABSTRACT: The automatic detection of engineering drawing modifications made by other designers is central to improving CAD/CAPP working efficiency levels. Engineering drawings include numerous entities, but only a few entities are modified. It is difficult for designers to identify modified entities in a complex drawing. This paper presents a novel means of detecting entities in engineering drawings created by other designers that employs semi-fragile watermark technologies. Modifications will change embedded watermarks. Consequently, detection is realized by analyzing changes. The approach was implemented, and the experimental results demonstrate that the method is reliable and can accurately detect entities that have been modified, deleted and added. GRAPHICAL ABSTRACT: